2002
DOI: 10.1021/es025805g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Speciation of Co(II), Ni(II), Cu(II), and Zn(II) in Model Solutions and Freshwaters:  Lability and the d Electron Configuration

Abstract: The kinetic speciation of Co(II), Ni(II), Cu(II), and Zn(II) in model solutions of a well-characterized fulvic acid (Laurentian fulvic acid), freshwater samples from the Rideau River (Ottawa, Ontario), and freshwater samples from the Sudbury (Ontario) area were investigated by the competing ligand exchange method using Chelex 100 as the competing ligand and by inductively coupled plasma-mass spectrometry to measure the dissociation kinetics. The metal species were quantitatively characterized by the rate coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 28 publications
1
30
1
Order By: Relevance
“…log K Co(II)EDTA = 16.45 vs. log K Co(III)EDTA = 41.4 (Martell and Smith, 1976)). In addition, strong octahedral Co(III) complexes are kinetically inert while Co(II) complexes are usually very labile (Soni and Soni, 2013), although slow Co(II) dissociation kinetics have been reported in some freshwater samples (Collins and Kinsela, 2010;Sekaly et al, 2002). Consequently, it is likely that the labile Co pool contains Co(II) species while the inert Co pool may include Co(III) or particularly inert Co(II) species.…”
Section: Ligand-exchange Kinetics -Labile and Inert Co Fractionsmentioning
confidence: 99%
“…log K Co(II)EDTA = 16.45 vs. log K Co(III)EDTA = 41.4 (Martell and Smith, 1976)). In addition, strong octahedral Co(III) complexes are kinetically inert while Co(II) complexes are usually very labile (Soni and Soni, 2013), although slow Co(II) dissociation kinetics have been reported in some freshwater samples (Collins and Kinsela, 2010;Sekaly et al, 2002). Consequently, it is likely that the labile Co pool contains Co(II) species while the inert Co pool may include Co(III) or particularly inert Co(II) species.…”
Section: Ligand-exchange Kinetics -Labile and Inert Co Fractionsmentioning
confidence: 99%
“…In earlier studies slow dissociation kinetics 80 of natural Ni-DOM complexes have been demonstrated [6,10,[13][14][15][16], however no data were 81 found on association kinetics. We used the Donnan speciation technique [17], a method which 82 minimizes the disturbance of the equilibrium composition in the test solution and which does 83 not rely on a priori knowledge of the conditional stability constant of a competing ligand.…”
Section: Page 11 Of 31mentioning
confidence: 99%
“…A weighed amount of chromium nitrate, Cr(NO 3 ) 3 .9H 2 O salt has been subjected to neutron irradiation in the CIRUS reactor,BARC,Mumbai with a neutron flux 1 x 10 12 n.cm -2 .s -1 .The nuclear reaction for the production of chromium radionuclide is 50 Cr(n,ϒ) 51 Cr.The half-life of 51 Cr is 27.7days and the ϒ-ray energy is 320.08 KeV. After irradiation the salt is dissolved in deionised water.…”
Section: Irradiationmentioning
confidence: 99%